2021
DOI: 10.1109/tnsre.2021.3055203
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Spatially Selective Retinal Stimulation With Temporally Interfering Electric Fields

Abstract: Retinal electrical stimulation is a widely utilized method to restore visual function for patients with retinal degenerative diseases. Transcorneal electrical stimulation (TES) represents an effective way to improve the visual function due to its potential neuroprotective effect. However, TES with single electrode fails to spatially and selectively stimulate retinal neurons. Herein, a computational modeling method was proposed to explore the feasibility of spatially selective retinal stimulation via temporally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The findings showed that TI electrical stimulation could work to increase voiding volume and decrease contraction frequency of the bladder, successfully inhibiting bladder activity. Besides, a computational modeling study aimed to explore the feasibility of spatially selective retinal stimulation via TIinduced electric fields (Su et al, 2021). According to the modeling results, TI stimulation with appropriate electrode montages could achieve selective and focal stimulation in a specific area of retinal neurons, whereas traditional transcorneal electrical stimulation could only stimulate the peripheral area of the retina.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The findings showed that TI electrical stimulation could work to increase voiding volume and decrease contraction frequency of the bladder, successfully inhibiting bladder activity. Besides, a computational modeling study aimed to explore the feasibility of spatially selective retinal stimulation via TIinduced electric fields (Su et al, 2021). According to the modeling results, TI stimulation with appropriate electrode montages could achieve selective and focal stimulation in a specific area of retinal neurons, whereas traditional transcorneal electrical stimulation could only stimulate the peripheral area of the retina.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Significant research efforts have focused largely on developing non-invasive or minimally invasive stimulation techniques (Boes et al, 2018 ; Sun et al, 2018 ; Guo et al, 2020 ; Su et al, 2021 , 2022 ; Lu et al, 2022 ; Ren et al, 2022 ). For example, transcranial direct current stimulation (tDCS) allows reversible region-specific modulation (Filmer et al, 2014 ).…”
Section: “The Greatest Victory Requires No Bleeding” — Chapter Strate...mentioning
confidence: 99%
“…Again it was shown that a single sine waveform is not able to cause stimulation [5]. Furthermore, TI has been studied for retinal stimulation [6]. Instead of using electrodes creating the electric field inside the brain, it is also possible to use TMS coils creating a magnetic field and inducing an electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Again it was shown that a single sine waveform is not able to cause stimulation [5]. Furthermore, TI has been studied for retinal stimulation [6].…”
Section: Introductionmentioning
confidence: 99%